Tracking Microplastics Contamination in Drinking Water Supply Chain in Haikou, China: From Source to Household Taps - Xiangxiang Li; Yihan Yu; Mei Yang; Shaobai Wen; Jun Zhang (Toxics)
The presence of microplastics (MPs) in aquatic environments has become a significant global concern due to their potential adverse effects on human health. This study aimed to investigate the contamination of MPs throughout the drinking water supply chain in Haikou City, China, and to conduct risk assessments regarding the relationship between MPs contamination and human health. The results revealed that the abundance of MPs in raw, treated, and tap water was 0.6 ± 0.6, 5.2 ± 2.7, and 1.2 ± 1.1 particles·L−1, respectively. Fragments were identified as the most prevalent shape across all samples, with the size category of 20–50 μm showing the highest abundance of MPs. Among the 11 types of polymers identified, polyethylene and polypropylene accounted for 50% and 29%, respectively. The potential risk index values were significantly higher for treated water (370.26) and tap water (303.85) compared to raw water (13.46), suggesting that plastic pipes may be a key contributor to MPs contamination in drinking water. Therefore, efforts should be directed toward developing pipes with low release rates of MPs, as well as improving detection methods for smaller particles and accurately assessing associated risks.